Use And Abuse Of Fuzzy Logic: Ethical Implications And The Nigerian Medical Practices - Ogbunkwu , Anacletus (International Journal of Psychosocial Rehabilitation, 2023)
This research investigates the ethical implications of the use and abuse of fuzzy logic in medical practice from a Nigerian perspective. In order to address the aim of this research appropriately, expository and analytical methods of research are employed to understand the dynamisms of use and abuse of fuzzy logic among Nigerian medical practitioners. Expository method serves to uncover the use of fuzzy logic in medical practice while analytic method gives a critical appraisal of the ethical implications in the abuse of fuzzy logic. Fuzzy logic is a multi-valued logic which describes the possibility of many truth values beyond just two-valued logic of yes and no. Fuzzy logic is a dependable support to scientific investigations and it serves medical practices in the following; health data gathering, diagnosis and decision making, analysis of Computer Tomography Scan, Magnetic Resonance Imaging (MRI), segmentation, feature extraction, specimen examination, etc. The use of fuzzy logic in medical practice is evaluated minding the following ethical demands; benevolence, non-maleficence, autonomy and justice. The use of fuzzy logic in medical diagnosis and treatment encounters challenges as follows; medical decisions from indirect indications, imprecisions, generation of wrong fuzzy data from inefficient equipment, presumptuous diagnosis, scrupulosity, compensational treatment, etc. The implication of this research is a clarion call on health workers to shun the flagrant abuses in the use of fuzzy logic in medical practice and the government to strengthen medical legal system in order to regain the confidence of the society in the medical system